A Green Synthesis of Carbene‐Metal‐Amides (CMAs) and Carboline‐Derived CMAs with Potent in vitro and ex vivo Anticancer Activity. (31st March 2022) - Tzouras, Nikolaos V.; Scattolin, Thomas; Gobbo, Alberto; Bhandary, Subhrajyoti; Rizzolio, Flavio; Cavarzerani, Enrico; Canzonieri, Vincenzo; Van Hecke, Kristof; Vougioukalakis, Georgios C.; Cazin, Catherine S. J.; Nolan, Steven P.
Abstract: The modularity and ease of synthesis of carbene‐metal‐amide (CMA) complexes based on the coinage metals (Au, Ag, Cu) and N‐heterocyclic carbenes (NHCs) as ancillary ligands pave the way for the expansion of their applications beyond photochemistry and catalysis. Herein, we further improve the synthesis of such compounds by circumventing the use of toxic organic solvents which were previously required for their purification, and we expand their scope to include complexes incorporating carbolines as the amido fragments. The novel complexes are screened both in vitro and ex vivo, against several cancer cell lines and high‐grade serous ovarian cancer (HGSOC) tumoroids, respectively. Excellent cytotoxicity values are obtained for most complexes, while the structural variety of the CMA library screened thus far, provides promising leads for future developments. Variations of all three components (NHC, metal, amido ligand), enable the establishment of trends regarding cytotoxicity and selectivity towards cancerous over normal cells. Abstract : Copper, silver, gold and green : A range of naturally occurring carboline alkaloid‐derived carbene‐metal‐amide (CMA) complexes of copper, silver, and gold are synthesized for the first time under mild and operationally simple conditions. A screening against cancer cell lines and tumoroids reveals excellent cytotoxicity and selectivity in certain cases. A green purification of the compounds is showcased, in light of their promising biological/pharmacological function.